Difference between revisions of "009A Sample Final 2, Problem 3"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam">Compute   <math>\frac{dy}{dx}.</math> <span class="exam">(a)  <math style="vertical-align: -15px">y=\bigg(\frac{x^2+3}{x^2-1}\bigg)^3</math> <sp...")
 
 
Line 88: Line 88:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|Let &nbsp;<math style="vertical-align: -5px">f(x)=\sin(x)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">g(x)=\sin^{-1}x.</math>
+
|Let &nbsp;<math style="vertical-align: -5px">y=\sin^{-1}(x).</math>&nbsp; Then,
 
|-
 
|-
|These functions are inverses of each other since
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\sin(y)=x</math>
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">f(g(x))=x</math>&nbsp; and &nbsp; <math style="vertical-align: -5px">g(f(x))=x.</math>
+
|for &nbsp;<math>y</math>&nbsp; in the interval &nbsp;<math>\bigg[-\frac{\pi}{2},\frac{\pi}{2}\bigg].</math>
 
|-
 
|-
|Therefore,
+
|Using implicit differentiation, we have
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\cos(y) \frac{dy}{dx}=1.</math>
\displaystyle{g'(x)} & = & \displaystyle{\frac{1}{f'(g(x))}}\\
 
&&\\
 
& = & \displaystyle{\frac{1}{\cos(\sin^{-1} x)}.}
 
\end{array}</math>
 
 
|-
 
|-
|Now, let &nbsp;<math style="vertical-align: -5px">y=\sin^{-1}(x).</math>&nbsp; Then, &nbsp;<math style="vertical-align: -5px">x=\sin(y).</math>
+
|Solving for &nbsp;<math style="vertical-align: -15px">\frac{dy}{dx},</math>&nbsp; we get
 
|-
 
|-
|So, &nbsp;<math style="vertical-align: -5px">\cos(\sin^{-1} x)=\cos(y).</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{dy}{dx}=\frac{1}{\cos(y)}.</math>
|-
 
|Therefore,
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>g'(x)=\frac{1}{\cos(y)}.</math>
 
 
|}
 
|}
  
Line 114: Line 106:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, since
+
|Now, since &nbsp;<math>\sin(y)=x,</math>&nbsp; we have the following diagram.
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\cos^2 y+\sin^2 y =1,</math>
+
|(Insert diagram)
 
|-
 
|-
|we have
+
|Therefore,
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\cos(y)=\sqrt{1-x^2}.</math>
 +
|-
 +
|Hence,
 
|-
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
\displaystyle{\cos(y)} & = & \displaystyle{\sqrt{1-\sin^2 y}}\\
+
\displaystyle{\frac{dy}{dx}} & = & \displaystyle{\frac{1}{\cos(y)}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\sqrt{1-x^2}.}
+
& = & \displaystyle{\frac{1}{\sqrt{1-x^2}}.}
 
\end{array}</math>
 
\end{array}</math>
|-
 
|Hence,
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math>g'(x)=\frac{1}{\sqrt{1-x^2}}.</math>
 
 
|}
 
|}
  

Latest revision as of 17:11, 20 May 2017

Compute  

(a)  

(b)  

(c)  

Foundations:  
1. Product Rule
       
2. Quotient Rule
       
3. Chain Rule
       


Solution:

(a)

Step 1:  
Using the Chain Rule, we have
       
Step 2:  
Now, using the Quotient Rule, we have
       

(b)

Step 1:  
Using the Product Rule, we have
       
Step 2:  
Now, using the Chain Rule, we get
       

(c)

Step 1:  
Let    Then,
       
for    in the interval  
Using implicit differentiation, we have
       
Solving for    we get
       
Step 2:  
Now, since    we have the following diagram.
(Insert diagram)
Therefore,
       
Hence,
       


Final Answer:  
   (a)   
   (b)   
   (c)   

Return to Sample Exam